(untitled) (Colombia Medica, 2008)
The use of bibliometrics indicators to study research activity is based on which the scientific publications are essential product of this activity, and provide information about the research process, its volume, evolution, visibility and structure. So, they allow to value the scientific activity, and influences (or impact) of the work and the sources. The bibliometrics studies, altogether with other indicators, allows an objective quantification of the knowledge, and are harnessed by the present explosion of the knowledge and its compilation in bibliographical data bases.